Multiple blood samples in elite soccer players. Is it worthwhile? - Heisterberg, M.; Fahrenkrug, J.; Andersen, J. (Journal of Sports Sciences, 2014)
Soccer at the elite level is a physical demanding game, and the physical challenges of the players have increased during the later years as the game has become more intense and matches more frequent. Among managers, physical coaches and the medical staff surrounding the modern professional soccer teams, there is a constant quest for even small adjustments that might improve the players` condition and performance. Changes in training type and amount, match participation, restitution, diet and various other aspects of the players` daily life can be made in order to maximise physical performance of the team or an individual player. Such changes can be based on general knowledge of physiology as well as empiric scientific experiments or sometimes pure intuition.